The Vision Detroit Project: Visual Burden, Barriers, and Access to Eye Care in an Urban Setting. (2nd January 2022) - Goyal, Anju; Richards, Collin; Patel, Vaama; Syeda, Sarah; Guest, John-Michael; Freedman, Ryan L.; Hall, Leo M.; Kim, Chaesik; Sirajeldin, Abdala; Rodriguez, Tannia; Arsenault, Samantha M.; Boss, Joseph D.; et al.
ABSTRACT: Purpose: Vision loss and blindness are among the top ten disabilities in the United States, yet access and utilization of eye care remains low. Vision Detroit aimed to address eye-care disparities via community-based screenings. By investigating burden of eye disease and barriers to eye-care utilization in an underserved urban community, we may direct efforts to improve access. Methods: Twenty-three screenings were conducted from March 2015-November 2017. Patient information gathered at screenings were demographics, medical and social history, eye exam/referral history, insurance status, primary care physician (PCP) status, and patient-perceived eye-care barriers. Results: Three-hundred-eighty patients were screened, 42% African American and 51% Hispanic. Average age was 53 ± 16.4 years, 70% reported vision problems, 50% reported over two years of vision problems, and average habitual visual acuity in best-seeing eye was 20/37. Eye-care underutilization was reported in 61% of type-2 diabetics. Older age and PCP recommendations/referrals were associated with increased utilization in all patients. Insurance was the most common barrier (53%); of the 55% insured, 31% reported financial barriers. Employed patients were more likely than unemployed to report a time barrier (odds ratio = 1.76, 95% confidence interval 1.03–3.01). Those with high school or less education reported "unaware of need", "unsure where to go", "transportation", and "insurance" as barriers more often. Conclusion: Visual burden was pervasive, yet access was suboptimal. Financial, logistical, and awareness barriers were common. PCP referral and older age were associated with increased utilization. Those less educated reported more barriers, highlighting the need to address fiscal concerns and eye-health education.